Forecasting the general surgery physician workforce deficit in the state of Georgia: a public health perspective. (October 2019) - Keipper, R.; Berman, A.E.
Abstract: Objectives: The aim of the study was to quantify the current shortage of general surgeons in the state of Georgia and to estimate the shortage in 2040. Study design: This is a population-based longitudinal study. Methods: Data were collected from the US Census Bureau, the Georgia Board for Physician Workforce, and the Accreditation Council for Graduate Medical Education to evaluate changes in the supply of general surgeons from 2000 to 2017 and estimate an expected shortage through 2040. Results: The state of Georgia experienced a net loss of 120 surgeons from 2000 to 2017 and currently faces a shortage of 139 general surgeons. We project a deficit of between 285 and 725 general surgeons in the state of Georgia by 2040. Conclusion: Georgia will face a substantial general surgical workforce shortage by 2040. Enhanced efforts at boosting both the output of surgical training programs as well as recruitment and retention of surgeons may help alleviate this deficit. Highlights: The state of Georgia has experienced a growth in the population accompanied by a loss of 120 general surgeons. Georgia currently has a calculated shortage of 139 general surgeons. Georgia is projected to have a shortage of between 285 and 725 general surgeons by 2040.